Development of two electronic bladder diaries: A patient and healthcare professionals pilot study. Issue 7 (2nd September 2013) - Mangera, Altaf; Marzo, Alberto; Heron, Nicola; Fernando, Dayan; Hameed, Khawar; Soliman, Abdel‐Hamid A.; Bradley, Mike; Hosking, Ian; Abdel‐Maguid, Mohamed; Levermore, Martin; Tindale, Wendy B.; Chapple, Christopher
Abstract Aims Assess patients' preferences in a pilot crossover study of two different electronic voiding diaries against a standard paper diary. Assess urological health professional (HP) opinions on the electronic bladder diary reporting system. Methods Two different electronic diaries were developed: (1) electronically read diary—a card with predefined slots read by a card reader and (2) e‐diary—a handheld touch screen device. Data uploaded from either electronic diary produced an electronic report. We recruited 22 patients split into two cohorts for each electronic diary, 11 completed each type of electronic diary for 3 days either preceded or followed by a standard paper diary for 3 days. Both diaries were completed on the 7th day. Patients' perceptions of both diaries were recorded using a standardized questionnaire. A HP study recruited 22 urologists who were given the paper diary and the electronic reports. Time taken for analysis was recorded along with accuracy and HP preferences. Results The majority of patients (82%) preferred the e‐diary and only 1/11 found it difficult to use. Patients had the same preference for the electronically read diary as the paper diary. The paper diary took 66% longer to analyze than the electronic report (P < 0.001) and was analyzed with an accuracy of 58% compared to 100%. Slightly more HP (9%) preferred the electronic report to the paper diary. Conclusions This proposed e‐diary with its intuitive interface has overcome previous deficiencies in electronic diaries with most patients finding the format user‐friendly. Electronic reports make analysis and interpretation by HP quicker and more accurate. Neurourol. Urodynam. 33:1101–1109, 2014. © 2013 Wiley Periodicals, Inc.